Examination of the Collective Argumentation Studies in the Mathematics Education Field - Ayşe Tekin Dede (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
Different socio-cultural theories have begun to be used in mathematics education studies, which have developed from individual learning to learning in its social context. One of these theories is the collective argumentation theory based on Toulmin's argumentation studies. The collective argumentation is dealt with as an interactive process in which students and teachers are claiming and supporting these claims through evidence. In this study, it is aimed to introduce similar and different aspects of the collective argumentation studies in the field of mathematics education by introducing it. As a result of the literature review carried out in this context, fourteen studies were encountered. The common feature of these studies is that each one is based on the teacher or student discourse, and that they use the components of Toulmin's argumentation schema to analyze these discourses. While some studies link different theoretical frameworks with argumentation, some aim to develop a theoretical framework and some aim to make conceptual presentations about the components of the argumentation. It is thought that the work to be done in different class contexts with different student groups and teachers will contribute to both the national and international fields because there are deficiencies in the studies in the field of the collective argumentation in our country.